Perceived Stigma, Social Support and Quality of Life in Patients of Tuberculosis: Quality of Life in Patients of TB - Akhtar, Nasreen; Batool, Iffat; Zohaib Khan, Muhammad (Pakistan Journal of Health Sciences, 2023)
Stigma associated with tuberculosis impairs the quality of life in the patients of this disease by causing delay in seeking treatment whereas the social support improves their quality of life. Objective: To find out the role of perceived stigma, and social support in predicting the quality of life among patients of tuberculosis. A correlational research design using a survey method was used in this research. The study was conducted in hospitals in Lahore during 2019-2020. Methods: The sample consisted of 200 patients with tuberculosis (99 men, 101 women). Urdu versions of the Perceived Stigma Scale, Multidimensional Scale of Perceived Social Support, and World Health Quality of Life were employed to collect data. Results: Pearson correlation analysis indicated that patients who perceived more social stigma had a significantly poor quality of life whereas those patients who perceived greater social support had a better quality of life. Furthermore, regression analysis indicated that social support appeared to be the strongest positive predictor for quality of life followed by stigma which appeared to be a negative predictor for quality of life in patients of tuberculosis. Conclusion: The findings of this study have important implications for mental health professionals, health psychologists, and medical practitioners.